Isolation and partial characterization of bacteriophages infecting Pseudomonas syringae pv. actinidiae, causal agent of kiwifruit bacterial canker. (9th May 2014) - Di Lallo, Gustavo; Evangelisti, Matteo; Mancuso, Francesco; Ferrante, Patrizia; Marcelletti, Simone; Tinari, Antonella; Superti, Fabiana; Migliore, Luciana; D'Addabbo, Pietro; Frezza, Domenico; Scortichini, Marco; Thaller, Maria Cristina
<x xml:space="preserve">Abstract</x> The phytopathogen Pseudomonas syringae pv. actinidiae (Psa) is the causal agent of bacterial canker of kiwifruit. In the last years, it has caused severe economic losses to Actinidia spp. cultivations, mainly in Italy and New Zealand. Conventional strategies adopted did not provide adequate control of infection. Phage therapy may be a realistic and safe answer to the urgent need for novel antibacterial agents aiming to control this bacterial pathogen. In this study, we described the isolation and characterization of two bacteriophages able to specifically infect Psa. φPSA1, a member of the Siphoviridae family, is a temperate phage with a narrow host range, a long latency, and a burst size of 178; φPSA2 is a lytic phage of Podoviridae family with a broader host range, a short latency, a burst size of 92 and a higher bactericidal activity as determined by the TOD value. The genomic sequence of φPSA1 has a length of 51, 090 bp and a low sequence homology with the other siphophages, whereas φPSA2 has a length of 40 472 bp with a 98% homology with Pseudomonas putida bacteriophage gh‐1. Of the two phages examined, φPSA2 may be considered as a candidate for phage therapy of kiwifruit disease, while φPSA1 seems specific toward the recent outbreak's isolates and could be useful for Psa typing.